LA-MRSA CC398 in Dairy Cattle and Veal Calf Farms Indicates Spillover From Pig Production - Hansen, Julie E.; Ronco, Troels; Stegger, Marc; Sieber, Raphael N.; Fertner, Mette E.; Martin, Henrik L.; Farre, Michael; Toft, Nils; Larsen, Anders R.; Pedersen, Karl (Frontiers in Microbiology, 2019)
The possible spillover from pigs into other production animals incites concern for unresolved reservoirs of human exposure. The present investigation was therefore initiated, to elucidate if Danish veal and dairy farms constitute a reservoir of livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) CC398 and to potentially identify the source of introduction. We collected nasal swab samples from 17 Danish veal farms, 2 slaughterhouses, and received bulk tank milk samples from 286 dairy farms. All samples were analyzed by culturing and screening on MRSA selective plates and presumed MRSA was verified by MALDI-TOF and PCR. MRSA isolates were subjected to spa typing and whole-genome sequencing. LA-MRSA was found on two veal farms in one and three calves, respectively, with subsequent follow-up samples found negative. Eight of 286 dairy farms (2.8%) were found LA-MRSA positive and follow-up samples, from five farms showed intermittent detection of LA-MRSA. The spa types, t034 and t011, were the most common while a single isolate from a dairy farm belonged to spa type t843 associated to mecC-MRSA CC130 and is the first report of mecC-MRSA in the Danish dairy production. A phylogenetic analysis showed that some of the isolates grouped within or close to the dominant Danish pig clusters, suggesting spillover into cattle farms. Other isolates clustered outside the dominant pig clusters suggesting that other routes of introduction cannot be excluded. Results of the investigation indicated a contamination of veal farms while some dairy farms seemed to be a permanent reservoir. Thus, Danish cattle represent a low prevalence reservoir of LA-MRSA CC398, which at present, is not of major human health concern.